APPLYING VALUE CREATION FRAMEWORK TO OFFER PUBLIC TRANSPORT IMPROVEMENT - Nanda Kurniawan; Ahmad Munawar (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
Public Transportation in urban areas is expected to be main choice for people’s mobility. The aim of this research is apply value creation framework based on S-D Logic and Trans Jogja from Yogyakarta and Värmlandstrafik AB Sweden are the case study. This research use direct observation and interview to the related person/ company as the primary data, and to support them use group discussion with the users. This research also use secondary data from some journals, reports, documentations, etc. From the analysis and discussion Värmlandstrafik AB is address the value creation service and opportunity more than Trans Jogja. From conclusion, the need of applying value creation framework in Trans Jogja is to offer public transport improvement as has been illustrated by Trans Jogja. Although the achievement of value creation opportunities are not as high as that achieved by Värmlandstrafik AB, but Trans Jogja should learn about what needs should be improved.Keywords: S-D Logic, Value Creation Opportunity, Trans Jogja, Public Transport Improvement